Implementation of green-assessed nanotechnology and quality by design approach for development of optical sensor for determination of tobramycin in ophthalmic formulations and spiked human plasma - Christine M. El-Maraghy; Passant M. Medhat; Rania M. Hathout; Miriam F. Ayad; Nermine V. Fares (BMC Chemistry, 2024)
Abstract A fast eco-friendly colorimetric method was developed for the determination of Tobramycin in drug substance, ophthalmic formulations, and spiked human plasma using silver nanoparticles optical sensor. Even though tobramycin is non-UV–visible absorbing, the developed method is based on measuring the absorbance quenching of silver nanoparticles resulting from the interaction with tobramycin. Different factors affecting the absorbance intensity were studied as; silver nanoparticle concentration, pH, buffer type, and reaction time using quality by design approach. Validation of the proposed method was performed according to ICH guidelines and was found to be accurate, precise, and sensitive. The linearity range of tobramycin was 0.35–4.0 μg/mL. The optical sensor was successfully applied for the determination of Tobramycin in ophthalmic formulations and spiked human plasma without pre-treatment. Additionally, the binding between Tobramycin and PVP- capped silver nanoparticles was studied using molecular docking software. The method was assessed and compared to colorimetric reported methods for the green character using Green Analytical Procedure Index (GAPI) and Analytical GREEnness calculator (AGREE) tools and found to be greener.